Efektivitas Pembelajaran Siswa SMP Secara Daring Selama Pandemi Covid 19 - Meri Januamita; Kiki Amelia (Universitas Negeri Padang, 2023)
The Covid-19 pandemic is increasing in Indonesia with the new finding of the Delta variant which resulted in many people dying from being exposed to Covid-19 so that online learning by the government was extended so as to make changes to all aspects of education. This study aims to find out about the obstacles felt by parents when accompanying or directing their children to study at home. This type of research uses a descriptive method, through interview, observation, and listening techniques. In this study, it is able to produce and show a general picture experienced by parents in accompanying children who have not been maximally studying at home during the Covid-19 period which is very unusually draining a lot of energy, emotions, time, quotas, internet networks, even parents are very complaining about learning that is given by virtual googlemeet or yuotube as well as materials using media such as whatshap, Google Class Room, Geschool, Gmeet followed by evaluations and assignments, eventually causing anxiety for parents who do not understand the material being taught online in class IX. During the pandemic, the role of parents is very important in supporting the success of children's achievements. Teachers in schools are requested to learn from home and focus on essential materials and tasks that are not burdensome and based on home activities. Technology (learning media) such as using Android phones, laptops, gadgets. This causes anxiety and confusion for parents who have different educational backgrounds. With strong motivation and making new innovations in guiding children, so that children are not bored and stressed in learning, there must be good coordination and communication between parents and teachers. Evaluation is needed in order to improve student achievement results.